2019
DOI: 10.1097/jhq.0000000000000142
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Teledermatology Service for Assessing Solitary Skin Lesions in a Tertiary London Dermatology Center

Abstract: Teledermatology can significantly reduce the number of urgent referrals necessitating FTF appointments, therefore providing a new solution to streamline care delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Although almost half of our TDS recruitment is generated outside our region, this high number is explained by the high proportion of nail conditions for which biopsy is difficult to conduct in home offices. Cheung et al also demonstrated that TD avoided FTF consultation in 68% of cases with good-quality pictures [22]. Dermoscopy picture quality was good in 89.7% of cases in our study, similar to Massone et al (88%) [14].…”
Section: Discussionsupporting
confidence: 89%
“…Although almost half of our TDS recruitment is generated outside our region, this high number is explained by the high proportion of nail conditions for which biopsy is difficult to conduct in home offices. Cheung et al also demonstrated that TD avoided FTF consultation in 68% of cases with good-quality pictures [22]. Dermoscopy picture quality was good in 89.7% of cases in our study, similar to Massone et al (88%) [14].…”
Section: Discussionsupporting
confidence: 89%
“…The factors related to service providers are also among other variables affecting the establishment of teledermatology in Iran. Young (2018) [29], Chang (2018) [33], Tol (2017) [34], Agnisarman (2017) [35], Van Derberg (2012) [32], and Oikonomu (2009) 19| Jorjani Biomedicine Journal. 2020; 8(1): P 11-23 [27] reported that the factors related to service providers affect the establishment of teledermatology.…”
Section: Discussionmentioning
confidence: 99%
“…Another variable affecting the establishment of teledermatology in Iran are the factors related to service recipients. The studies conducted by Rajda [15], Chang [33], Manarao (2018) [22], Tol (2017) [34], Campaigna (2017) [36], Livit (2016) [35], and Neuilu (2016) [30] showed that the factors related to service recipients also affect the establishment of teledermatology. The results of this study indicated that the most important factor in this regard was patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Teledermatology has consistently been reported to be highly effective for triage and subsequently reducing time to treatment for urgent cases and reducing unnecessary referrals for patients whose skin condition can be effectively managed by primary care . In a recent primary study, 68% of in‐person appointments were avoided using teledermatology for triage to identify patients that had a benign lesion . Other primary studies have found similar results identifying potentially between 40‐66% of in‐person visits as avoidable as a result of teledermatology triage …”
Section: Evidence For Teledermatologymentioning
confidence: 91%
“…Mobile phone applications are increasingly being used for SAF teledermatology . Secure email and integrated electronic medical records to share images between the referrer and provider are alternative methods of implementing SAF teledermatology. To facilitate SAF, the Guidelines describe minimum technical standards for clinical photography and dermoscopy.…”
Section: Teledermatology Practicementioning
confidence: 99%